IP-based services over GPRS. - Chitre, Vikrant A.
The utility of mobile computing in the future will be determined to a large degree by the quality of service achievable over cellular based systems. In this paper, we examine the traffic-handling capabilities of General Packet Radio Service (GPRS) with respect to supporting IP-based Internet services. We begin with an overview of GPRS. We then present an analytical model to assess throughput of the reverse link as a function of the number of users connected and the distribution of user message lengths for a scenario in which users are continuously backlogged. Next, we investigate the capability of GPRS to support World Wide Web access using a modified version of the analytical model. Specifically, we present a realistic scenario for user sessions operating under the Hypertext Transfer Protocol (HTTP), and we assess the transaction-handling capabilities as a function of the number of user sessions, taking into account network delays, forward link transmission, random access delay, and other factors. We also consider a scenario where both continuously backlogged users and users operating HTTP sessions are present. We conclude with a discussion of some open issues in the design of GPRS based Internet access.
Keywords: Computer systems organization; Computer communication networks; Network architecture and design; Wireless Communication; Mathematics of computing; Probability and statistics; Queueing theory; Computing methodologies; Simulation and modeling; Design; Measurement; Performance; Standardization; Theory; IP over wireless; Cellular data service; Queues with contention